Guilt and grace - Tournier, Paul 1898-1986 (UK Highland, 1962)
Includes bibliographical references and index.
Originally published by Delachaux and Niestle, S.A. with the title "Vrai ou Fausse Cupabilite"
Keywords: Guilt -- religious aspects -- Christianity; Grace -- religious aspects -- Christianity